Popularity of international fitness franchise "Tapout Fitness" in Bangladesh: Current attractiveness and the future - khan, Samit Saif Bari (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.